Evaluation of a docetaxel-cisplatin-fluorouracil-Au complex in human oral carcinoma cell line - Wannisa Khamaikawin; Kitsakorn Locharoenrat (Artificial Cells Nanomedicine and Biotechnology, 2023)
Higher tobacco and alcohol use have led to a consistent increase in head and neck cancer incidence rates. Currently employed chemotherapeutic and surgical treatment are associated with significant drawbacks. Herein, we evaluated the anti-tumour effect of gold nanoparticles as a vehicle for the delivery of a triple chemotherapy drug formulation and elucidated the potential underlying mechanism. The hydrodynamic size of docetaxel, cisplatin, and 5-fluorouracil physically co-adsorbed on Au nanoparticles was 56 ± 0.8 nm, showing a negative zeta potential. Fourier transform infra-red spectroscopy data confirmed that the triple chemotherapy drug successfully interacted with the gold nano-carrier. Au nanoparticles exhibited high loading efficacy of docetaxel (61%), cisplatin (75%), and 5-fluorouracil (90%), with a controlled drug release profile at 24 h. The triple chemotherapy drug formulation was tested in human oral cavity cancer cell line (KB). Cytotoxicity achieved through a synergistic effect between the treatments led to apoptosis, with a lower half-maximal inhibitory concentration indicating higher cytotoxicity than that of plain docetaxel-cisplatin-fluorouracil. Taken together, we demonstrated that the docetaxel-cisplatin-fluorouracil-gold complex exhibited excellent cytotoxicity in KB cells, superior to that docetaxel-cisplatin-fluorouracil.HIGHLIGHTSThe docetaxel-cisplatin-fluorouracil-Au complex showed a controlled drug-release profile at 24 h.The docetaxel-cisplatin-fluorouracil-Au complex exhibited enhanced internalisation efficiency in cells.Au nanoparticles were biocompatible, with no change in apoptosis among cell line.Spherical Au nanoparticles allowed a high volume of incorporated docetaxel, cisplatin, and 5-fluorouracil to steadily attach onto cells.
Keywords: Nanoparticle-Based Drug Delivery; Dendrimers and Hyperbranched Polymers; Advanced biosensing and bioanalysis techniques